(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract : This research aims to study the factors that affect the spread of hate speech on social media platforms. The survey method was used, where data was collected through designing a questionnaire and distributing it to a sample of Iraqi university students in Baghdad. The results showed that there are several factors that affect the spread of hate speech on social media platforms, including: 1- There is a statistically significant relationship between social media platforms and the spread of hate speech. 2- The results confirmed, based on the sample respondents’ answers, that forms of publication have the highest impact on the spread of hate speech via social media platforms. 3- The research sample individuals confirmed that hate speech consists of rumors and false information that some individuals use to exclude and marginalize others. 4- Most of the sample’s opinions agreed that publishing videos, texts, and offensive images has a significant role in inciting hatred towards others. 5- The sample individuals agreed that those with extremist religious tendencies have the most influence in spreading hate speech. Based on these results, the research recommends dealing with social media platforms cautiously by raising awareness among community members about the necessity of not publishing content and media messages that target individuals or groups based on their religious, sectarian, or ethnic affiliations. Social media publishing is a form of freedom of expression and personal freedom in publishing, provided that the general decorum conditions are not violated .It also involves making social media platforms neutral tools that are not misused, avoiding spreading hate speech, and not arousing historical topics of dispute to fuel conflicts and strife.